2005
DOI: 10.1080/10641950500281068
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester Sex Hormone-Binding Globulin and Subsequent Development of Preeclampsia or Other Adverse Pregnancy Outcomes

Abstract: First trimester maternal serum SHBG concentrations are no different from controls in women who subsequently develop preeclampsia, pregnancy-induced hypertension, fetal growth restriction, or preterm delivery. Levels are reduced in those who subsequently miscarry or in those presenting with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…Spencer et al [26] reported lower SHBG concentration in the first trimester of pregnancy in women who developed GDM. A recent study [13] showed that preconception SHBG levels were better predictors of GDM in PCOS women compared with waist circumference or HOMA-IR.…”
Section: Discussionmentioning
confidence: 99%
“…Spencer et al [26] reported lower SHBG concentration in the first trimester of pregnancy in women who developed GDM. A recent study [13] showed that preconception SHBG levels were better predictors of GDM in PCOS women compared with waist circumference or HOMA-IR.…”
Section: Discussionmentioning
confidence: 99%
“…), would be closely related to the onset of stillbirths during the first trimester and of pathologies affecting the mother-child binomial. The etiopathogenesis of such conditions would involve endothelial dysfunction and/or predisposing metabolic conditions having an abnormal placentation, as that seen in PE, as a common denominator [17,18,19,20,21,22]. PE shares a series of pathophysiological findings with IR, among which are the following: endothelial dysfunction, atherosclerosis and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Our result of lower SHBG in hypertensive women with gestational diabetes mellitus compared with those with normal blood pressure could indicate increased risk for type 2 diabetes in the former. Earlier studies on SHBG in gestational diabetes as well as in hypertensive pregnancy complications compared with normal pregnancy have shown controversial results [35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 97%